OBTAINING OF RECOMBINANT PROTEIN FRAGMENT OF THE GP51 ANTIGEN VIRUS OF BOVINE LEUKEMIA EXPRESSED IN E.COLI WITHOUT INSERT THIOREDOXIN - Mukantayev , K.N.; Shustov , A.B.; Sydyknabi , I.; Bigalyeva , A.; Raiymbek , G.; Mukanov , K.K. (Eurasian Journal of Applied Biotechnology, 2014)
Glycoprotein gp51 and the main structural protein p24 leucosis virus of livestock animals are the main diagnostic antigens. In this case, the most significant part of the eresearch is devoted to obtaining recombinant antigens. As a source of gp51 and p24 antigen is a virus which the cell lines derived from fetal lamb kidney (FLK) that, chronically infected with the virus. The current method is inefficient and time-consuming, also, very low yield of the final product. In the last decades, many studies have been done on the expression of Env glycoprotein gene in heterologous systems such as Escherichia coli, Saccharomyces cerevisiae, as well as in the system of the recombinant vaccinia virus and more recently, in the baculovirus system. In previously published work we had described recombinant gp51 antigen based on the expression vector pET32 that gene-carrying thioredoxin. However, the use of the resulting antigen gp51 + thioredoxin in diagnostic test systems proved undesirable due to significant cross-reactions to thioredoxin, which is unacceptable in the development of high-performance test systems, such as immunochromatographic or enzyme immunoassays. In this case, the purpose of the work was to produce recombinant gp51 protein of livestock leucosis in E. coli without thioredoxin expression. In the process used immunological, biochemical, serological and biotechnology research. As a result of this study, the gene of hexahistidine tags was added on the 3 ’end of the viral protein gp51 gene of livestock leucosis, after then, the gene was cloned into an expression vector E3.pET22. The transformation of the vector which carrying the gen of leucosis virus gp51. Identified the parameters of the gp51 protein expression strains that transformed by microorganisms and proved various analytical and immunochemical methods for expression of the desired protein.